Effects of technology-integrated formative assessment on students' conceptual and procedural knowledge in chemical equilibrium - Tadesse Hagos; Dereje Andargie (Intelektual Pustaka Media Utama, 2023)
The impacts of a technology-integrated formative assessment technique on students' conceptual and procedural knowledge in studying chemical equilibrium are studied in this study. To attain the purpose, a quasi-experimental pretest-posttest strategy nested with a qualitative study method was adopted. The study has three groups: two experimental and one comparative. A random sample strategy was utilized to select two intact classes for treatment and one intact class for comparison groups. Data was collected using the chemical equilibrium conceptual test, the procedural test, and classroom observation. The data was examined using descriptive (mean and standard deviation) and inferential statistics (one-way ANOVA, one-way MANOVA, and Pearson product moment correlation). According to the findings, technology-integrated formative assessment processes outperformed traditional techniques and formative assessment strategies alone in enhancing students' conceptual and practical understanding of chemical equilibrium. Similarly, when technology-integrated formative assessment processes are used, classroom observations show that students have a strong motivation to learn and that the instructor is more skilled than the other two teachers. Technology-integrated formative assessment processes were shown to be more effective than the other two groups in promoting students' conceptual and procedural understanding when learning chemical equilibrium.